SHOTCRETE DELIVERY PROCESS DI TAMBANG BAWAH TANAH DEEP MILL LEVEL ZONE PT FREEPORT INDONESIA - Mahatir Eko Sulastyo; Jance Murdjani Supit (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
In ground support of underground mine, it is important to understand the shotcrete delivery process, since shotcrete is the main buffer applied. The problem found in this study is that there is an indication that the shotcrete volume has not matched the reported shotcrete. So it is important to acknowledge the shotcrete delivery process, the difference in volume and the correction factor. Variables used to calculate shotcrete volume and correction factors obtained in nine main variables as follow: shotcrete trace length, shotcrete trace width, shotcrete trace height, shotcrete transfer distance, shotcrete transfer time, shotcrete transfer time, material weight, material density and shotcrete volume in the Daily Report. Descriptive statistical method is used to select anomaly data outside the population. The research results that average volume of shotcrete on the Batch Plant is 4.83 m³, then transferred to WS Mixer reduced to 4.76 m³ and at Getman the Mixer was reduced by 3.92 m³. The volume difference is due to the unequal aggregate conditions of the shotcrete constituents, the Mixer drum rotates outside the specified speed, shotcrete hardening occurs on the drum causing a reduction in drum volume capacity. Based on these differences, conversion values were obtained to the reported shotcrete volume, which is 0.87 with the shotcrete assumption reported at 4 m³, 0.89 assuming 5 m³ and 0.79 assuming 4.98 m³.